2016
DOI: 10.1155/2016/6837241
|View full text |Cite|
|
Sign up to set email alerts
|

Dual Effects of Cellular Immunotherapy in Inhibition of Virus Replication and Prolongation of Survival in HCV-Positive Hepatocellular Carcinoma Patients

Abstract: Immune cells play an important role in the development and progression of hepatitis C virus (HCV) and hepatocellular carcinoma (HCC). We conducted a retrospective study to evaluate the influence of adoptive cellular immunotherapy (CIT) on viral load and progression-free survival (PFS) for HCC patients infected with HCV. Patients (n = 104) were divided into a control group (conventional therapy, n = 73) and study group (combination of CIT and conventional therapy, n = 31). Autologous mononuclear cells were indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…None of the studies reported immunotherapy-related hospital mortality. Only 23 patients in four studies[23,29,32,36] were reported with grade III or IV adverse events. Fever was addressed as the most common event after immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies reported immunotherapy-related hospital mortality. Only 23 patients in four studies[23,29,32,36] were reported with grade III or IV adverse events. Fever was addressed as the most common event after immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Even though gene modification approaches, such as CAR technology, have achieved ground-breaking success in CD19+ diseases, [3][4][5] the application of such a strategy in solid tumors is still under continuous investigation. Notably, the published literature has intensively reviewed the clinical potential of Vγ9Vδ2 T cells as a new strategy for cancer immunotherapy; [13][14][15]22,23 for instance, previous clinical trials on non-small cell lung cancer, 10,46 hepatocellular carcinoma 47 renal cell carcinoma, [48][49][50][51] and myeloma 52 proved the feasibility of Vγ9Vδ2 T cells in tumor immunotherapy. However, limited clinical efficacy 26 makes Vγ9Vδ2 T cells of modest value in clinical investigation and application.…”
Section: Discussionmentioning
confidence: 99%
“…Zoledronate induces the proliferation of γδ T cells in HCC patients who exhibit upregulated expression of IFN-γ, TNF-α, GrB, perforin, and lysosome-associated membrane protein 1 ( 47 ). A clinical trial has shown that the combined use of γδ T cells, NK cells, and cytokine-induced killer (CIK) therapy significantly inhibits virus replication and prolongs the survival rate of HCV-positive HCC patients ( 21 ).…”
Section: Role Of γδ T Cells In Liver Cirrhosis and Hccmentioning
confidence: 99%
“…Similar contradictory functions are also observed in other stages. In HCC, human Vδ2 T cells, which can be activated and proliferate in vitro ( 20 ), are used in the clinic to prolong the survival time of HCC patients ( 21 ).…”
Section: Introductionmentioning
confidence: 99%